Oral health history in children referred to a child advocacy center in Norway. (October 2022) - Toft, Julie; Myhre, Arne Kristian; Sun, Yi-Qian; Willumsen, Tiril; Rønneberg, Anne
Abstract: Background: Some suspected child victims of physical or sexual abuse undergo dental forensic examinations at child advocacy centers (CACs) in Norway. Their oral health history has not previously been studied. Objective: This study aimed to compare oral health history of CAC children to matched children. Additionally, the oral health history of children exposed to sexual abuse was compared to children exposed to physical abuse. Participants and setting: The CAC cohort included 100 children, 3–16 years. The matched cohort, with no known history of abuse, included 63 children. Methods: The retrospective study analyzed registered data in the children's dental records. Results: CAC children were more likely than matched children to have caries experience in both primary and permanent teeth, with incidence rate ratio (IRR) 1.50 (95 % CI 1.01–2.25) and 1.92 (1.11–3.30). "Was Not Brought" to dental appointments was more than twice as likely, IRR 2.25 (1.31–3.86), in the CAC cohort. There were no significant differences in reports to the Child Protection Services or dental traumas. Suspected victims of sexual abuse had more caries, IRR 4.28 (2.36–7.77), and fillings, IRR 4.83 (2.55–9.16), in permanent teeth compared to suspected victims of physical abuse. Conclusions: CAC children were more likely to have caries experience and not show up for dental appointments than the matched children. Sexual abuse suspected had four times more caries experience than physical abuse suspected. This study supports the need for addressing oral health in risk evaluations concerning child abuse, and provides valuable information to dental professionals and prosecuting authorities.